New Horizons for the Roles and Association of APE1/Ref-1 and ABCA1 in Atherosclerosis - Chen W; Wang S; Xing D (Dove Medical Press, 2021)
Wujun Chen,1 Shuai Wang,2 Dongming Xing1,3 1Cancer Institute, The Affiliated Hospital of Qingdao University, Qingdao University, Qingdao Cancer Institute, Qingdao, Shandong, 266071, People's Republic of China; 2School of Medical Imaging, Radiotherapy Department of Affiliated Hospital, Weifang Medical University, Weifang, Shandong, 261053, People's Republic of China; 3School of Life Sciences, Tsinghua University, Beijing, 100084, People's Republic of ChinaCorrespondence: Dongming XingCancer Institute, The Affiliated Hospital of Qingdao University, Qingdao University, Qingdao Cancer Institute, Qingdao, Shandong, People's Republic of ChinaTel +86-532- 82991017Email xdm_tsinghua@163.comShuai WangSchool of Medical Imaging, Radiotherapy Department of Affiliated Hospital, Weifang Medical University, Weifang, Shandong, People's Republic of ChinaTel +86-536-8462228Email sdwftcmws@163.comAbstract: Atherosclerosis is the leading cause of death worldwide. APE1/Ref-1 and ABCA1 play key roles in the progression of atherosclerosis. APE1/Ref-1 suppresses atherosclerosis via multiple mechanisms, including reducing the IL-6-, TNF-α-, and IL-1β-mediated proinflammatory responses, suppressing ROS-mediated oxidant activity and Bax/Bcl-2-mediated vascular calcification and apoptosis, and reducing LOX-1-mediated cholesterol uptake. However, APE1/Ref-1 also promotes atherosclerosis by increasing the activity of the NK-κB and S1PR1 pathways. APE1/Ref-1 localizes to the nucleus, cytoplasm, and mitochondria and can be secreted from the cell. APE1/Ref-1 localization is dynamically regulated by the disease state and may be responsible for its proatherogenic and antiatherogenic effects. ABCA1 promotes cholesterol efflux and anti-inflammatory responses by binding to apoA-I and regulates apoptotic cell clearance and HSPC proliferation to protect against inflammatory responses. Interestingly, in addition to mediating these functions, ABCA1 promotes the secretion of acetylated APE1/Ref-1 (AcAPE1/Ref-1), a therapeutic target, which protects against atherosclerosis development. The APE1/Ref-1 inhibitor APX3330 is being evaluated in a phase II clinical trial. The LXR agonist LXR-623 (WAY-252623) is an agonist of ABCA1 and the first LXR-targeting compound to be evaluated in clinical trials. In this article, we review the roles of ABCA1 and APE1/Ref-1 in atherosclerosis and focus on new insights into the ABCA1-APE1/Ref-1 axis and its potential as a novel therapeutic target in atherosclerosis.Keywords: atherosclerosis, inflammatory, APE1/Ref-1, ABCA1, cholesterol efflux